Parental status is related to homing motivation in males of the glassfrog Centrolene savagei. Issue 5 (3rd September 2021) - Navarro-Salcedo, Paula; Duarte-Marín, Sebastián; Rada, Marco; Vargas-Salinas, Fernando
Abstract : The interaction between homing and parental care offers insights about the motivational aspects underlying movement patterns in animals. For species that care for offspring at fixed locations, offspring mortality in the absence of care might impact a parent's motivation to home after being displaced from young. We tested whether homing motivation is related to parental care in the glassfrog Centrolene savagei (Centrolenidae), a species with extended male care and territoriality. Specifically, we evaluated how parental status (i.e. caring for eggs vs unmated yet territorial males) and translocation distance impacts homing motivation. Along a stream located in the Central Andes of Colombia, we translocated 23 male C. savagei between 5 and 80 m away from their reproductive territories. We found that both parental status and translocation distance impacts homing motivation, as caring males were more likely to return to their initial territories after translocation. Seven of the 16 caring males and one of the seven unmated males returned to the initial capture site. While unmated males might be motivated to home if reproductive territories are a limited resource, our results support that caring males exhibited much higher motivation to home. It is possible that the fitness benefits accrued from caring for vulnerable offspring alters the cost-to-benefits of homing, and thus accounts for a greater frequency of homing among caring males. This study contributes to understanding how aspects of life history (e.g. parental care) relate to homing motivation in vertebrates.